Targeted tumor radiotherapy - Unak,Perihan (2002)
Targeted tumor radiotherapy is selectively delivery of curative doses of radiation to malignant sites. The aim of the targeted tumor radiotherapy is to use the radionuclides which have high LET particle emissions conjugated to appropriate carrier molecules. The radionuclides are selectively collected by tumor cells, depositing lethal doses to tumor cells while no admission occur to normal cells. In theory, targeted radiotherapy has several advantages over conventional radiotherapy since it allows a high radiation dose to be administered without causing normal tissue toxicity, although there are some limitations in the availability of appropriate targeting agents and in the calculations of administered doses. Therefore, for routine clinical applications more progress is still needed. In this article, the potential use of targeted tumor radiotherapy is briefly reviewed. More general aspects and considerations, such as potential radionuclides, mechanisms of tumor targeting was also outlined.